CACNA1E variants affect beta cell function in patients with newly diagnosed type 2 diabetes. the Verona newly diagnosed type 2 diabetes study (VNDS) 3. - Maddalena Trombetta (Public Library of Science (PLoS), 2012)
Background Genetic variability of the major subunit (CACNA1E) of the voltage-dependent Ca(2+) channel Ca(V)2.3 is associated to risk of type 2 diabetes, insulin resistance and impaired insulin secretion in nondiabetic subjects. The aim of the study was to test whether CACNA1E common variability affects beta cell function and/or insulin sensitivity in patients with newly diagnosed type 2 diabetes. Methodology/principal findings In 595 GAD-negative, drug naïve patients (mean ± SD; age: 58.5 ± 10.2 yrs; BMI: 29.9 ± 5 kg/m(2), HbA1c: 7.0±1.3) with newly diagnosed type 2 diabetes we: 1. genotyped 10 tag SNPs in CACNA1E region reportedly covering ∼93% of CACNA1E common variability: rs558994, rs679931, rs2184945, rs10797728, rs3905011, rs12071300, rs175338, rs3753737, rs2253388 and rs4652679; 2. assessed clinical phenotypes, insulin sensitivity by the euglycemic insulin clamp and beta cell function by state-of-art modelling of glucose/C-peptide curves during OGTT. Five CACNA1E tag SNPs (rs10797728, rs175338, rs2184945, rs3905011 and rs4652679) were associated with specific aspects of beta cell function (p<0.05-0.01). Both major alleles of rs2184945 and rs3905011 were each (p<0.01 and p<0.005, respectively) associated to reduced proportional control with a demonstrable additive effect (p<0.005). In contrast, only the major allele of rs2253388 was related weakly to more severe insulin resistance (p<0.05). Conclusions/significance In patients with newly diagnosed type 2 diabetes CACNA1E common variability is strongly associated to beta cell function. Genotyping CACNA1E might be of help to infer the beta cell functional phenotype and to select a personalized treatment.